[Me2C{SnCH(SiMe3)2}2]2. A μ-Me2C-bridged tetrastanna tetrahedrane12. Issue 1 (12th November 2014) - Wagner, Michael; Lutter, Michael; Zobel, Bernhard; Hiller, Wolf; Prosenc, Marc H.; Jurkschat, Klaus
Abstract : A spacer-bridged bis(organostannylene) was obtained adopting the structure of a doubly capped tetrahedron in the solid state. Its reaction with elemental oxygen provided organotin suboxides. Abstract : A spacer-bridged bis(organostannylene) was obtained. In the solid-state it adopts the structure of a doubly-capped tetrahedron. It reacts with elemental oxygen, O2, giving tin suboxides. Additionally, the first solid state structure of a spacer-bridged diorgano tin dihydride is reported.